Accuracy of cervical pedicle screw placement with four different designs of rapid prototyping navigation templates: a human cadaveric study. Issue 1 (1st January 2021) - Wen, Zhijing; Lu, Teng; He, Xijing; Li, Jialiang; Zang, Quanjin; Wang, Yibin; Gao, Zhengchao; Gu, Pengzhen
Abstract: Purpose: Due to the high perforation rate of cervical pedicle screw placement, we have designed four different types of rapid prototyping navigation templates to enhance the accuracy of cervical pedicle screw placement. Methods: Fifteen human cadaveric cervical spines from C2 to C7 were randomly divided into five groups, with three specimens in each group. The diameter of pedicle screw used in this study was 3.5 mm. Groups 1–4 were assisted by the two-level template, one-level bilateral template, one-level unilateral template and one-level point-contact template, respectively. Group 5 was without any navigation template. After the surgery, the accuracy of screw placement in the five groups was evaluated using postoperative computed tomographic scans to observe whether the screw breached the pedicle cortex. Results: A total of 180 pedicle screws were inserted without any accidents. The accuracy rate was 75%, 100%, 100%, 91.7%, and 63.9%, respectively, from Groups 1 to 5. All the template groups were significantly higher than Group 5, though the two-level navigation template group was significantly lower than the other three template groups. The operation time was 4.72 ± 0.28, 4.81 ± 0.29, 5.03 ± 0.35, 8.42 ± 0.36, and 10.05 ± 0.52 min, respectively, from Groups 1 to 5. The no template and point-contact procedures were significantly more time-consuming than the template procedures. Conclusion: This study demonstrated that four different design types of navigation templates achieved a higher accuracy in assisting cervical pedicle screw placement than no template insertion. However, the two-level template's accuracy was the lowest compared to the other three templates. Meanwhile, these templates avoided fluoroscopy during the surgery and decreased the operation time. It is always very challenging to translate cadaveric studies to clinical practice. Hence, the one-level bilateral, unilateral, and point-contact navigation templates designed by us need to be meticulously tested to verify their accuracy and safety.